Mass spectrometry reveals potential of b-lactams as SARS-CoV-2 Mpro inhibitors - Malla, T.R.; Tumber, A.; John, T.; Brewitz, L.; Strain-Damerell, C.; David Owen, C.; Lukacik, P.; Henry Chan, H.T.; Pratheesh, M.; Zihe Rao; Zihe Rao, M.A.; Schofield, C.J. (The Royal Society of Chemistry, 2021)
The main viral protease (Mpro) of SARS-CoV-2 is a nucleophilic cysteine hydrolase and a current target for anti-viral chemotherapy. We describe a high-throughput solid phase extraction coupled to mass spectrometry Mpro assay. The results reveal some b-lactams, including penicillin esters, are active site reacting Mpro inhibitors, thus highlighting the potential of acylating agents for Mpro inhibition.